Does financial inclusion promote financial stability? Evidence from Africa - Yawovi M. A. Koudalo; Moumbark Toure (Cogent Economics & Finance, 2023)
This study aims to examine the impact of financial inclusion on financial stability across 54 African countries. Using country-level data that spans a 20-year period from 2000 to 2020, the findings suggest a positive association between the level of account penetration and financial stability. This conclusion withstands several tests of robustness performed. Furthermore, the analysis identifies income inequality, political stability and financial openness as influential factors that may condition the relationship between financial inclusion and financial stability. The implications of our findings suggest the need for increased collaboration between regulatory and supervisory agencies in African countries to promote greater financial inclusion, as policies aimed at improving financial inclusion should have the potential to enhance financial stability. It should be noted, however, that the extent to which financial inclusion should be pursued in order to achieve these goals remains an open question that requires further investigation. Future research could also explore the key barriers to financial access, as identifying these obstacles would enable policymakers to set priorities for action and allocate resources more effectively.
Keywords: G21; G28; O55; 330; African countries; Financial inclusion; financial institutions; financial stability; risk